Hubungan Indeks Massa Tubuh dengan Kolesterol, LDL, dan Trigliserida pada Pasien Jantung Koroner di Kota Banda Aceh - Agus Hendra Al Rahmad (Jurnal Kesehatan, 2021)
Obesity is a form of excessive fat composition in a person's body and allows increased levels of lipids in the blood so it is very risky in patients with coronary heart disease (CHD). The parameter used in identifying obesity as a form of nutritional status in adults is body mass index (BMI). Being overweight is synonymous with several non-communicable diseases, one of which is CHD. The study aimed to measure the relationship of BMI with cholesterol, LDL, and triglyceride in CHD patients in Banda Aceh City. The study used a cross-sectional design, which was conducted at several hospitals in Banda Aceh City with a sample of 28 outpatient CHD patients. Characteristic data collection was carried out by interview using a questionnaire, body weight, height, and BMI data were collected through anthropometric measurements, while lipid profile data (cholesterol, LDL, and triglyceride levels) were collected through laboratory examination of colorimetric chemical methods with UV-VIS spectrophotometer. Data analysis using Pearson Correlation test on CI: 95%. The results showed a significant relationship between BMI with cholesterol levels (p= 0,001) and triglyceride levels (p= 0,027), and had moderate and positive correlation strengths. In contrast, BMI with LDL levels did not show a significant relationship (p= 0,192). Conclusion, BMI has a positive effect on cholesterol and triglyceride levels, but it is not significant in increasing LDL levels in CHD patients in Banda Aceh City. Suggestion, CHD patients need to do a healthy lifestyle and consume balanced food and do physical activities such as running, biking, walking fast routinely.  Keywords: Cardiovascular, cholesterol, LDL, obesity, triglycerides